The Profitability of Austrian Foreign Direct Investment - Reinvestment or Repatriation? - W. Altzinger (FIW - Research Centre International Economics, 2008)
Austrian foreign direct investment (FDI) increased quickly since 1992. The profitability of these investments did improve over the full period under consideration (1992 to 2005). In particular investments in Central and Eastern Europe became rather profitable. In 2005 total annual profits translate into an average return on equity (RoE) of 8.3%. However, returns differ to a large extent by regions. They are 5.1% and 9.7% for EU-14 and for CEE-5 respectively. The age of investment is the main determinate of profitability. Interestingly, there are strong differences between Greenfield investments and M&As. While the latter are always more profitable in EU-15 this is not the case for affiliates in CEE. In these countries we can observe a time-dependent development. During the first years of investments M&A are more profitable than Greenfield investments. However, the latter become more rewarding by older vintages. We further examine if profits are either reinvested (and thereby contribute to the existing stock of capital in the host country) or repatriated (and thereby improve the performance of home countries). The paper shows that patterns differ substantially by countries and over time. The share of reinvestment is much higher in CEE than in EU-15. Moreover, M&A show much higher rates of repatriation than Greenfield investments independent of host countries.
Keywords: 330; Foreign direct investment; profitability; EU enlargement; greenfield investment and M&As